(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
This study was conducted in Al-Kufra oasis deep in the Libyan Desert (Sahara Desert). The aim was to evaluate the role of Vachellia nilotica trees in improving soil properties and creating islands of fertility even in a hyper-arid and degraded ecosystem. In three different plots, a systematic sampling procedure consisting of four soil samples collected from each tree from the uppermost layer of the soil (0-30 cm). The first was close to the tree trunk, the second was under the middle of the tree canopy, the third was under the canopy edge, and the fourth was collected from the inter-canopy zone away from the canopy edge. Tree characteristics and crown architecture were investigated for each tree. The study revealed that the mean levels of the examined nutrients in the under-canopy significantly differed from the adjacent inter-canopy zone. Total soil nitrogen, phosphorus, and organic matter contents were significantly higher, and the soil pH values were significantly lower (p < 0.05) under than inter-canopy zone. This study illustrated the vital role of indigenous Vachellia nilotica trees in creating islands of fertility and improving soil properties under their canopies over time without any active intervention, even in the hyper-arid and harsh environments as in the Sahara Desert.